The Integration of Multimodality in EFL Classes: Students’ Perception - Khalif Arfazul Ilmi; Dian Novita Dewi (Universitas Pendidikan Mandalika, 2022)
Technology has greatly influenced education in the twenty-first century. Multimodal teaching is one of many classroom methods brought by technology. However, only a few studies have been conducted on how to create a multimodal pedagogy to assist EFL students in enhancing their language skills. Therefore, the purpose of this study was to investigate the perceptions of high school English students regarding the integration of multimodality into English classroom practices. Participation in this study was determined using a random sample. Data was gathered from 100 high school students in SMA Panjura, Malang. These students have experienced using multimodal in their learning process for six weeks. In this research, a quantitative method with a survey research design was chosen. The data were analyzed using SPSS 24 and the data was presented descriptively. The study revealed that the majority of students had a positive attitude toward the implementation of multimodality in their learning process in response to the characteristics of current students.